MicroRNA profiling of cerebrospinal fluid from dogs with steroid responsive meningitis-arteritis and meningoencephalitis of unknown origin - Mármol-Sánchez, Emilio; Heidemann, Pernille Lindholm; Gredal, Hanne; Cirera, Susanna (Frontiers in Veterinary Science, 2023)
Noninfectious inflammatory diseases of the central nervous system in dogs, such as steroid responsive meningitis-arteritis (SRMA) and meningoencephalitis of unknown origin (MUO), represent a common clinical challenge that needs extensive and multimodal work-up to reach a presumptive diagnosis. Both diseases are presumably caused by dysregulations of the immune system, but further research is needed in order to understand the molecular mechanisms behind each disease and to optimize treatment. By next-generation sequencing and subsequent quantitative real-time PCR (qPCR) verification, we designed a prospective case-control pilot study to analyze the small RNA profiles of cerebrospinal fluid from dogs suffering from MUO (N = 5), dogs suffering from SRMA (N = 8), and healthy dogs (N = 5) presented for elective euthanasia used as the Control group. Our results showed an overall enrichment in Y-RNA fragments across all samples, followed by microRNAs (miRNAs) and ribosomal RNAs as the major findings. Additional traces of short RNA reads mapped to long non-coding RNAs and protein-coding genes were also found. From the detected canine miRNAs, miR-21, miR-486, miR-148a, miR-99a, miR-191 and miR-92a were among the most abundant. Dogs with SRMA showed higher differences in miRNA abundance than dogs with MUO when compared to healthy dogs, and miR-142-3p was consistently detected as differentially upregulated in both diseases, although at a low concentration. Moreover, miR-405-5p and miR-503-5p showed different profiles between SRMA and MUO dogs. Subsequent qPCR analyses confirmed miR-142-5p, miR-191-5p and miR-92a-3p as significantly upregulated miRNAs in dogs with SRMA and/or MUO. Cerebrospinal fluid is a challenging biological material to use for profiling miRNAs due to the low content of circulating RNAs. Despite this, we could confirm several miRNAs being differentially abundant when comparing healthy dogs and dogs with MUO and SRMA, respectively. The results of this study indicate a potential role of miRNAs in the underlying molecular mechanisms of these diseases and establish the basis for further studies.